Novel origin of lamin-derived cytoplasmic intermediate filaments in tardigrades - Lars Hering; Jamal-Eddine Bouameur; Julian Reichelt; Thomas M Magin; Georg Mayer (eLife, 2016)
Intermediate filament (IF) proteins, including nuclear lamins and cytoplasmic IF proteins, are essential cytoskeletal components of bilaterian cells. Despite their important role in protecting tissues against mechanical force, no cytoplasmic IF proteins have been convincingly identified in arthropods. Here we show that the ancestral cytoplasmic IF protein gene was lost in the entire panarthropod (onychophoran + tardigrade + arthropod) rather than arthropod lineage and that nuclear, lamin-derived proteins instead acquired new cytoplasmic roles at least three times independently in collembolans, copepods, and tardigrades. Transcriptomic and genomic data revealed three IF protein genes in the tardigrade Hypsibius dujardini, one of which (cytotardin) occurs exclusively in the cytoplasm of epidermal and foregut epithelia, where it forms belt-like filaments around each epithelial cell. These results suggest that a lamin derivative has been co-opted to enhance tissue stability in tardigrades, a function otherwise served by cytoplasmic IF proteins in all other bilaterians.